The structure of investment arbitration - Cole, Tony (Routledge, 2013)
"Although a State's treatment of foreign investors has long been regulated by international law, it is only recently that international investment law has emerged as an independent discipline in its own right. Prior to the rise to importance of investment arbitration, international investment disputes were predominantly handled by specialists in public international law, and were resolved using the generally-applicable rules of that discipline. Over recent decades, however, the practical success of investment arbitration has allowed international investment law to develop both its own cadre of academic and professional specialists and its own legal doctrines. However, because of its relative newness as a discipline international investment law is still characterised by the disagreement that accompanies the creation of any new field. As a result of this disagreement, broad consensus is difficult to gain on any topic, as even the strongest arguments reflect a perspective on the discipline that is not universally shared.This book analyses the structure of international investment law, as it has developed through the practice of investment arbitration in order to see how a variety of international investment law doctrines should be understood and applied. The book demonstrates how a structural analysis can shed light on several major controversies within investment law, including whether investment arbitration tribunals should be strongly influenced by the decisions of earlier tribunals, whether most-favoured nation clauses can serve as the basis for jurisdiction of an investment arbitration tribunal, and even what an investment actually is"--